Exploring Leadership Styles of Managers in Iraqi Kurdistan: The Role of National and Organizational Cultures Will Be Investigated - Hassan, Sardar (International Journal of Psychosocial Rehabilitation, 2019)
This study investigates the relationship between national and organizational culture and organizational leadership. A deep literature review of the past study was established. In order to explore the leadership styles in both private and public sector organizations in Iraqi Kurdistan and answer the research questions, the perceived styles of 272 managers were measured. Through MLQ 5X survey questionnaires by Avolio and Bass (2004), data were gathered and evaluated. Also to examine the research hypotheses and investigate the relationship between variables, both multi-regression and correlation coefficient tests were used. Additionally, national culture and organizational culture were regressed on organizational leadership, and the opposite was conducted too. The managers’ perception results indicate that organizations in both sectors are dominated by laissez-faire and transactional leadership behaviors. The findings from analyses also suggest that there is a positive relationship between variables. The results demonstrated that both national culture and organizational culture influence different leadership styles in organizations in Iraqi Kurdistan. Moreover, the test result also indicated that leadership style, particularly laissez-faire as the dominant style, is a strong predictor of both dominant organizational culture types in Iraqi Kurdistan.